Influence of definition and data collection on the incidence of injuries in football - Junge, A.; Dvorak, J. (The American Journal of Sports Medicine, 2000)
Studies on the incidence of football injuries vary in the definition of injury, study design, methods of data collection, and observation periods. The aim of this study was to review the different methodologies applied in the evaluation of football injuries as well as to analyze the influence of data collection methods on the incidence of football injuries. In this study, injury data obtained weekly by a physician during 1 year of follow-up in 264 football players were compared with the results of retrospective questionnaires completed by the players at the end of the observation period. In the retrospective questionnaire, the incidence of injuries as well as of complaints was significantly lower than that found in the weekly follow-up examinations. Approximately every third moderate injury and less than 10% of the mild injuries were remembered retrospectively. The shorter the period of symptoms and the longer ago the injury occurred, the more frequently it was forgotten. However, even severe injuries, such as fractures, were not reported in the retrospective investigation. Based on the review of the literature and the data presented, recommendations in relation to study design, the definition of injury, and the calculation of incidence are proposed.